Projection invariant $t$-Baer and related modules - Kara, Yeliz (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 512.5We investigate the concepts of projection invariant $t$-extending modules and projection invariant $t$-Baer modules, which are generalized to those $π$-extending and $t$-Baer notions, respectively. Several structural properties are obtained and some applications are developed. It is proved that the $π$-$t$-extending modules and $π$-$t$-e. Baer modules are connected with each other. Moreover, we obtain a characterization for $π$-$t$-extending modules relative to the annihilator conditions.